Keadilan Hukum dan Penerapannya dalam Pengadilan - Ruman, Yustinus Suhardi (Humaniora, 2012)
This paper describes the legal justice. There is a view that justice is based on the provisions of law. This means that a fair punishment would be called as fair when the punishment was in accordance with the provisions of law. This view does not question whether the content or provision of the law is fair or not. According to the authors, legal justice is not only dependent on the provision of law, but also the content of the law itself. Justice is fair, not only depend on the provisions of the law, but also on the content of the law. The content of the law must be built on the principles of fair respect for human dignity. It is means that the law is fair, not merely because that law is applied to everyone, but also it is not contrary to human dignity.